X‐irradiation effects on thymidine kinase (TK): II. The significance of deoxythymidine triphosphate for inhibition of TK1 activity - He, Q. (Cell Prolif, 2002)
Abstract. The purpose of this study was to investigate the mechanism behind the high sensitivity of thymidine kinase 1 (TK1) to X‐irradiation. The deoxythymidine triphosphate (dTTP) pool was studied in mouse ascites tumour cells 1–24 h after X‐irradiation with 5 Gy. Irradiation changed the Michaelis‐Menten kinetics of TK1 from linear to biphasic, showing a negative co‐operativity. These changes were closely related to changes in the dTTP pool. Addition of dTTP to the cell extract of non‐irradiated cells, or thymidine (dTdR) to the culture medium, resulted in changes very similar to the kinetics found in the irradiated cells. Addition of 5¢‐amino‐5¢‐deoxythymidine (5¢‐AdTdR), a thymidine analogue that eliminated the inhibitory effect of dTTP on TK1 activity, completely abolished the irradiation‐induced inhibition of TK1 activity. We suggest that the reduced TK1 activity is mainly due to an elevated intracellular concentration of dTTP.